The Danish Scale for visual rating of massive weight loss body contours. Conceptualization and construct. Issue 4 (4th July 2019) - Berg, Jais Oliver; Rosenkrantz Hölmich, Lisbet; Printzlau, Andreas
Abstract: The 'Danish Scale' (DS) is a visual rating scale of massive weight loss body contour deformities and excessive skin in female MWL-patients with current BMI< 30 kg/m 2 and massive weight loss defined as BMI loss (delta-BMI)> 15 kg/m 2, regardless of weight loss method. The scope of the scale is to simplify the reporting of objective findings by a three-step grading of minor, moderate and severe body contour changes in six different body regions: breasts, abdomen, upper back, buttocks, arms and legs. The DS is presented with descriptions of the conceptualization and construct of the scale. It provides a new visual reference tool for indications and preoperative planning in MWL body contouring, that is specific for the post-MWL BMI-range between 21 and 30 kg/m 2 and, at the same time, simpler than previous scales. The scale combines evaluations of different and adjacent body regions in a simple manner and presents modern cut-off points for health insurance reimbursement for MWL body contouring as offered in the Danish public health care system. The DS was developed by repeat expert discussions until final nationwide consensus was reached and can act as an adjunct to the written guidelines by the National Board of Health in Denmark.